2022
DOI: 10.4103/ijmr.ijmr_3332_21
|View full text |Cite
|
Sign up to set email alerts
|

Non-communicable diseases as a major contributor to deaths in 12 tribal districts in India

Abstract: Background & objectives: Non-communicable diseases (NCDs) are the leading cause of death in India. Although studies have reported a high prevalence of NCD in tribal populations, there are limited data pertaining mortality due to NCDs. Therefore, in this study we estimated the proportion of deaths due to NCDs among 15 yr and older age group in tribal districts in India. Methods: We conducted a community-based survey in 12 districts (one per State) with more than 50 per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…23 Recent studies on the tribal population in India have reported that NCD related deaths have surpassed deaths due to infectious diseases. 24,25 This may be attributed to the early epidemiologic transition in this population as mentioned in the tribal health report submitted to the Government of India by Dr Abhay Bang et al 26 This study concludes that the most common neoplasm seen is in the Thyroid (64%) followed by GIT (10.5%). Populations residing in hilly areas of the country are usually considered to be high risk groups for thyroid disorders 27,28 and that is consistent with the findings of this study as well.…”
Section: Discussionmentioning
confidence: 85%
“…23 Recent studies on the tribal population in India have reported that NCD related deaths have surpassed deaths due to infectious diseases. 24,25 This may be attributed to the early epidemiologic transition in this population as mentioned in the tribal health report submitted to the Government of India by Dr Abhay Bang et al 26 This study concludes that the most common neoplasm seen is in the Thyroid (64%) followed by GIT (10.5%). Populations residing in hilly areas of the country are usually considered to be high risk groups for thyroid disorders 27,28 and that is consistent with the findings of this study as well.…”
Section: Discussionmentioning
confidence: 85%
“…Non-communicable diseases contribute to around 66% of deaths in adults in India. (10) Early detection by screening is vital for reducing morbidity and mortality. The sickle gene is widespread among many tribal population groups in India with prevalence of heterozygotes varying from 1-40 per cent.…”
mentioning
confidence: 99%